Gender, gambling settings and gambling behaviours among undergraduate poker players. Issue 1 (2nd January 2016) - Kairouz, Sylvia; Paradis, Catherine; Monson, Eva
Abstract: A gender divide in gambling is commonly observed among college populations. This study examines whether settings where students gamble on poker mediate the relationship between gender and poker gambling behaviours. Undergraduate poker players, 126 females and 242 males, were randomly sampled from three universities in Montreal, Canada. Three outcomes measuring risky behaviours were considered: severity of gambling problems as measured by the Problem Gambling Severity Index (PGSI), past-year poker spending and past-year poker debt. Multiple mediation analyses were conducted. The effect of gender on outcomes was analysed through three putative mediators: gambling on poker in private residences, in public locations or on the Internet. Male gender positively relates to risky gambling behaviours and occurrence of gambling in various settings. Risky gambling behaviours are positively related to gambling in various settings. Overall, the occurrence of playing poker in public locations and on the Internet emerged as significant mediators in relation to PGSI score, past-year poker spending and past-year poker debt. Given the nature of the processes by which gender is related to risky gambling behaviours among undergraduate students, gambling needs to be understood through a perspective that focuses as much on contexts as it does on individuals.